The role of servant leadership in enhancing organizational loyalty for workers: An analytical Research at the Oil Products Distribution Company / Karbala branch - Moonsor Khudhair, Samer; Salim Mohammad, Yazan (Iraqi Journal for Administrative Sciences, 2024)
This research aims to explore the relationship between servant leadership and worker loyalty through the characteristics of the leader, through examining a sample of employees in the Oil Products Distribution Company / Karbala branch, where (150) forms were distributed (132) of which was the response rate ( 88%), the research determined with a major hypothesis that there are two correlations of relationship and influence with statistically significant between servant leadership and organizational loyalty, the data was collected by questionnaire form, the researcher used a set of analytical methods including (simple correlation coefficient, simple linear regression coefficient, explanation coefficient R2(statistical program (SPSS23) was used to process data and test its validity, as the results showed the validity of the main and subsidiary assumptions and the researcher came out with a set of conclusions and recommendations, perhaps the most prominent of which is the necessity of adopting a servant leadership style by the departments in the company under study because of its great role in enhancing the level of Employee loyalty to her.